2002
DOI: 10.4049/jimmunol.168.2.744
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Signaling in B Cells Regulates the Expression of the Pim-1 Kinase Via the NF-κB Pathway

Abstract: The ability of CD40 signaling to regulate B cell growth, survival, differentiation, and Ig class switching involves many changes in gene expression. Using cDNA expression arrays and Northern blotting, we found that CD40 signaling increased the mRNA levels for pim-1, a protooncogene that encodes a serine/threonine protein kinase. Subsequent experiments showed that CD40 engagement also increased both Pim-1 protein levels and Pim-1 kinase activity in B cells. We then investigated the signaling pathways by which C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 95 publications
2
59
0
1
Order By: Relevance
“…5C). This finding agrees with other studies showing that NFκB signaling regulates Pim-1 expression in B cells (46). Overall, these data show that NFκB and Pim-1 regulate each other in CD8 T cells and may function to preserve a continuum of NFκB signaling when antigenic/ inflammatory signals are low or not present.…”
Section: Tcr-dependent Nfκb Signaling Is Required For Eomes Expressionsupporting
confidence: 82%
“…5C). This finding agrees with other studies showing that NFκB signaling regulates Pim-1 expression in B cells (46). Overall, these data show that NFκB and Pim-1 regulate each other in CD8 T cells and may function to preserve a continuum of NFκB signaling when antigenic/ inflammatory signals are low or not present.…”
Section: Tcr-dependent Nfκb Signaling Is Required For Eomes Expressionsupporting
confidence: 82%
“…It has been shown that the NF-kappa B pathway is involved in PIM1 regulation. 5 This would fit well with the fact that high PIM1 expression mainly is found in activated B-cell like DLBCL (ABC), which are characterized by constitutive activation of the NF-kappa B pathway. 4 Recently, it was shown that that inhibitors of IkappaB kinase (IKK) are toxic for ABC DLBCL cell lines, but not for cell lines derived from the germinal center like DLBCLs.…”
supporting
confidence: 52%
“…U0126 (New England Biolab) is a potent and specific inhibitor of MEK-1/2, and SB202190 (Calbiochem, La Jolla, CA) is a specific inhibitor of p38. Bay11-7082 and Bay11-7085 (both from Calbiochem) are specific inhibitors of I B phosphorylation (30)(31)(32). U0124 and SB202474 (both from Calbiochem) are control compounds for U0126 and SB202190, and these do not inhibit MEK-1/2 and p38 enzymatic activity, respectively.…”
Section: Effects Of Specific Inhibitors Of Mapk or Nf-b Pathways On Tmentioning
confidence: 99%